Thermo-mechanical properties of epoxidized hemp oil-based bioresins and biocomposites - Manthey, Nathan W. (2013)
Novel epoxidized hemp oil-based biocomposites containing jute fibre reinforcement were produced at the Centre of Excellence in Engineered Fibre Composites (CEEFC) owing to the need to develop new types of biobased materials. Mechanical properties (tensile, flexural, Charpy impact and interlaminar shear), thermo-mechanical properties (glass transition temperature, storage modulus and crosslink density) and moisture-absorption properties (saturation moisture level and diffusion coefficient) were investigated and compared with samples containing commercially produced epoxidized soybean oil and a synthetic bisphenol A diglycidyl ether-based epoxy control, R246TX cured with a blend of triethylenetetramine and isophorone diamine. Scanning electron microscopy was also performed to investigate the fibre–matrix interface. Epoxidized hemp oil-based samples were found to have marginally superior mechanical, dynamic mechanical and similar water-absorption properties in comparison to samples made with epoxidized soybean oil bioresin; however, both sample types were limited to bioresin concentrations below 30%. Synthetic epoxy-based samples exhibited the highest mechanical, dynamic mechanical and lowest water-absorption properties of all investigated samples. This study has also determined that epoxidized hemp oil-based bioresins when applied to jute fibre-reinforced biocomposites can compete with commercially produced epoxidized soybean oil in biocomposite applications.